Constraints on asymmetric production of long-lived scalars at the Large Hadron Collider - Thomas Chehab; Louie Dartmoor Corpe; Andreas Goudelis; Abdelhamid Haddad; Louise Millot (European Physical Journal C: Particles and Fields)
Abstract Searches for pair-produced long-lived particles (LLPs) at the LHC commonly operate under the assumption that the two LLPs are identical. In this paper we entertain the possibility that the targeted final states are, instead, induced by a LLP pair with different masses and/or lifetimes. We propose a simple and intuitively-parametrised toy model in order to study such asymmetric production of LLPs. Using the recasting material of a recent search for displaced jets by the ATLAS collaboration, we demonstrate that we can set constraints on the production cross-section times branching fraction into jets for a variety of asymmetric LLP and mediator mass combinations.